Health education for early detection of breast cancer - Silva, Andréa Rosane Sousa; Alves, Estela Rodrigues Paiva; Barros, Mariana Boulitreau Siqueira Campos; Bushatsky, Magaly; Souto, Cláudia Maria Medeiros Ramos; Figueira Filho, Antônio Simão dos Santos (Rev Rene, 2011)
The aim of this research was to access the impact of health education activities in the control of breast cancer in the district of Orobó, Pernambuco, Brazil. An action research was carried out in the Family Health Units with 246 women. The study was held from July 2007 to January 2008, before and after the performance of educative activities, with the application of pre- and post-tests to the participants. A family history of breast cancer was found in 20.32% of the women. When questioning on the risk factors that cause breast cancer it was demonstrated an increased knowledge on the part of women, resulting from the awareness after the lectures. With regard to those who did not know how to describe one or another step of self-examination, a significant decrease was observed through the answers, with 43.09% in the pre-test and 10.16% in the post-test. The actions allowed the identification of women at risk and their referral to the mastology unit of the Oswaldo Cruz University Hospital, in Recife, PE.